Innovative Efficiency of Russian Regions: Spatial Background and Spillovers Effects - Yuri PREOBRAZHENSKIY; Anna FIRSOVA (Communications of International Proceedings, 2020)
Innovations are an effective tool for economic development, becoming a defining element of the international competitiveness of countries and regions. The assessment of the innovative activities effectiveness in the regions of Russia allows us to distinguish two groups of regions: those from which knowledge spreads, and those where it is directed and gives an innovative effect. The largest Russian generators of knowledge (in terms of R&D expenditures) show extremely low efficiency of innovation activity, while a number of other regions with a minimum of R&D expenditures demonstrate impressive results. This situation can only arise as a result of the knowledge transfer demonstrated in this article. The research could be important in terms of policy implications for the management of innovation processes and will contribute to making informed decisions on the strategic directions of the development of regional innovation systems.
Keywords: Innovation; Knowledge Spillover; Regional Innovative Activity; Spillover of Innovations.